2003
DOI: 10.1890/0012-9658(2003)084[0463:mamodb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Mechanisms of Disequilibrium Between Predawn Plant and Soil Water Potentials

Abstract: Predawn plant water potential (Ψw, measured with leaf psychrometers) and surrogate measurements made with the pressure chamber (termed Ψpc here) are used to infer comparative ecological performance, based on the expectation that these plant potentials reflect the wettest soil Ψw accessed by roots. There is growing evidence, however, that some species exhibit substantial predawn disequilibrium (PDD), defined as plant Ψw or Ψpc at predawn substantially more negative than the Ψw of soil accessed by roots. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 42 publications
(66 reference statements)
6
116
2
8
Order By: Relevance
“…Hence, we may question whether ΨPD is truly in equilibrium with soil water potential in our system, since we would expect the lowest ΨPD measurements in the relatively shallow rooted P. sylvestris trees. One possible reason for this disequilibrium could be nocturnal sap flow [57], which has been demonstrated in Q. ilex trees in our study site [32]. However, P. sylvestris at our site also show some nocturnal sap flow during nights with high VPD [38], making it an unlikely explanation for the differential ΨPD patterns across species.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexmentioning
confidence: 81%
“…Hence, we may question whether ΨPD is truly in equilibrium with soil water potential in our system, since we would expect the lowest ΨPD measurements in the relatively shallow rooted P. sylvestris trees. One possible reason for this disequilibrium could be nocturnal sap flow [57], which has been demonstrated in Q. ilex trees in our study site [32]. However, P. sylvestris at our site also show some nocturnal sap flow during nights with high VPD [38], making it an unlikely explanation for the differential ΨPD patterns across species.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexmentioning
confidence: 81%
“…The disequilibrium between plant and Y soil early in the season was probably attributable to nocturnal transpiration or incomplete overnight rehydration of the above-ground portion of the trees (Bucci et al 2005). It has been shown that nocturnal transpiration can prevent overnight equilibration between plant and Y soil (Donovan, Linton & Richards 2001, Donovan, Richards & Linton 2003Bucci et al 2004a). Later in the season, Y soil in the morning fell below that of B. crassa and B. salicifolius roots, the species with the shallowest roots (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Donovan et al (2001) observed disequilibrium in the predawn hours between plant and soil water potentials in 16 of the 21 plant species tested. Donovan et al (2003) also reported disequilibrium between plant and soil water potentials in plants from the genera Chrysothamnus and Sarcobatus. James et al (2006), working with plants from the genus Sascorbatus under saline conditions, observed disequilibrium of great magnitude between the plant and the soil.…”
Section: Rwc Osmotic Watermentioning
confidence: 88%